Community-engaged research enhances the scientific quality and societal impact of a long-term avian monitoring program in northwest Ecuador - Karubian, Jordan; Olivo, Jorge; Cabrera, Domingo; Freile, Juan; Browne, Luke; Anderson, H. Luke; Cabo, Jairo; Paladines, Gregory; Loor, Gloria; Perlin Wilde, Liat (Frontiers in Conservation Science, 2025)
IntroductionThere has been a growing realization that a more inclusive approach to research can provide both ethical and practical benefits. Long-term avian monitoring programs, and indeed the academic and research community as a whole, are still learning how best to implement these methodologies effectively. MethodsThis paper provides information on a twenty-plus-year effort to conduct community-engaged avian monitoring in northwest Ecuador, with a focus on how this approach has impacted the quality and scope of the project’s science and broader societal impacts. We focus on three case studies that have been proceeding for varying lengths of time to highlight various stages of project development and maturity.ResultsA community-engaged approach has improved the quality of our scientific research by adding traditional ecological knowledge (TEK), technical capacity, and intellectual contributions to our monitoring efforts. Community-engaged research has also enhanced the breadth and quality of societal impacts, in terms of education, capacity building, and conservation, particularly in the formation of an ecological reserve that protects threatened species and habitat. We also discuss systemic and local challenges, and potential strategies to overcome these challengesDiscussionWe conclude that community-engaged research can improve the intellectual merit and broader societal impacts of long-term avian monitoring, and we advocate for continued investment, efforts, and careful reflection on best practices in this space.